1994
DOI: 10.1080/02626669409492740
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Akaike Information Criterion in the identification of an optimum flood frequency model

Abstract: For a long time now, the hydrologist has been faced with the problem of finding which of the many possible probability distribution functions can be used most effectively in flood frequency analyses. This problem has been mainly due to the insufficiency of the conventional goodness-of-fit procedures when used with the typically skewed flood probability distributions. In this study, the Akaike Information Criterion (AIC) goodness-of-fit test is used to identify more objectively the optimum model for flood frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…[6] Applications of model selection criteria within the field of the frequency analysis of hydrological extremes are rare and nonmethodical: In the works by Turkman [1985], Mutua [1994], Hache et al [1999], Strupczewski et al [2001Strupczewski et al [ , 2002 and Cahill [2003] the Akaike information criterion is applied to single case studies without, however, analyzing the properties of such criterion for small samples or comparing its selection efficiency with that of other criteria. Mitosek et al [2006] applied three model discrimination procedures in order to find the best fitting distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Applications of model selection criteria within the field of the frequency analysis of hydrological extremes are rare and nonmethodical: In the works by Turkman [1985], Mutua [1994], Hache et al [1999], Strupczewski et al [2001Strupczewski et al [ , 2002 and Cahill [2003] the Akaike information criterion is applied to single case studies without, however, analyzing the properties of such criterion for small samples or comparing its selection efficiency with that of other criteria. Mitosek et al [2006] applied three model discrimination procedures in order to find the best fitting distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The result of AIC is directly dependent with the sample size of observation [23]. AIC is asymptotically effective and unbiased since the test is based on the maximum likelihood function and if the sample size is sufficiently larger than 30, the test will yield fairly accurate result [24]. The sample size of this study is greater than 30, hence AIC can be applied to determine the best model.…”
Section: Goodness-of-fit Tests (Gof)mentioning
confidence: 98%
“…In Kenya, hydrological drought frequency studies are few and scattered and except for work by Mutua (1993) and Opere (1999) who fitted several distributions to maximum flow in the Lake Victoria, Rift Valley, Athi and the Tana basins and found the Wakeby and the three-parameter lognormal distributions to be the best models for flood frequency analysis, no comprehensive study has been done to fit frequency distribution models to hydrological drought events. In examining hydrological drought events using stream flow records, it is necessary to differentiate droughts from low flows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Low flows differ from droughts in that the duration in low flows is of the order of days or weeks, flows occur instantaneously and only one event is selected from an annual period of data. The various frequency distributions used by Mutua (1993) and Opere (1999) in modelling floods in the country are useful in hydrological drought frequency analysis. However, their suitability or otherwise has not been examined and except for preliminary studies by Sharma (1996) who has shown drought duration and severity at selected gauging stations in the country to follow the three parameter lognormal distribution, no previous attempt has been made to test the suitability of various frequency distribution models in modelling drought duration and severity in the Tana basin.…”
Section: Literature Reviewmentioning
confidence: 99%